Automated fiducial point selection for reducing registration error in the co-localisation of left atrium electroanatomic and imaging data. - Ali,RL; Cantwell,CD; Qureshi,NA; Roney,CH; Phang,Boon Lim; Sherwin,SJ; Siggers,JH; Peters,NS (IEEE, 2015)
Registration of electroanatomic surfaces and segmented images for the co-localisation of structural and functional data typically requires the manual selection of fiducial points, which are used to initialise automated surface registration. The identification of equivalent points on geometric features by the human eye is heavily subjective, and error in their selection may lead to distortion of the transformed surface and subsequently limit the accuracy of data co-localisation. We propose that the manual trimming of the pulmonary veins through the region of greatest geometrical curvature, coupled with an automated angle-based fiducial-point selection algorithm, significantly reduces target registration error compared with direct manual selection of fiducial points.